(untitled) (Research, Society and Development, 2022)
Introduction: The physician’s ways of relating to the patient tend to adopt biomedical models, which are simpler and impersonal, to the detriment of biopsychosocial models, which are more complex and with greater emotional demand. Among the various interventions proposed for the development and facilitation of the doctor-patient relationship are the Balint groups. Objective: To evaluate the participation in Balint groups in the development of a patient-centered attitude in the context of the doctor-patient relationship in relation to non-participants. Methods: Qualitative study of a phenomenological nature, with a sample composed of 30 participants, including medical students and physicians. Data collection took place in 2021 through narrative interviews. Results: Six ways were found to characterize what is essential in the encounter with the patient: Empathy; Effective Communication; Biopsychosocial View; Time; Physician Availability; Infrastructure. Seven “units of meaning” characterized the difficulties encountered in the encounter with the patient: Limitations of Access to Health; Ineffective Communication; Insecurities of the assistant physician; Difficult Patients; Patient Expectation; Excessive Work Load; Addressing Sensitive Matters. Three “units of meaning” were used by both groups to exemplify when the meeting with the patient was successful: Understanding the health-disease process; Medical Contribution; Patient gratitude. Conclusion: It was noticed, from the interviews, similarities between the groups, which present an optimistic view regarding the human and integral care of their patients, even with different approaches.